2014
DOI: 10.9734/bjpr/2014/6072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Dissolution and Bioavailability of Tamoxifen Citrate Loaded Binary and Ternary Solid Dispersions

Abstract: MKG managed the analyses of the study. Author MST managed the literature searches. Author MST run experiments and performed the statistical analysis. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Our findings agree with a previously reported T max of 4 to 7 hours for free TC [27]. Past work has shown that the elimination of TC is biphasic with a first-phase half-life of 7 hours and a terminal half-life of 7-11 days [2830]. As a result, TC has two values of elimination rate constant, K at 0.098 h-1 487 (initial half-life) and 0.004 h-1 381 (terminal half-life).…”
Section: Resultssupporting
confidence: 93%
“…Our findings agree with a previously reported T max of 4 to 7 hours for free TC [27]. Past work has shown that the elimination of TC is biphasic with a first-phase half-life of 7 hours and a terminal half-life of 7-11 days [2830]. As a result, TC has two values of elimination rate constant, K at 0.098 h-1 487 (initial half-life) and 0.004 h-1 381 (terminal half-life).…”
Section: Resultssupporting
confidence: 93%
“…The DSC thermogram of pure TMC showed a sharp endothermic peak at 145.8 °C (figure 3, C) corresponding to its melting point and indicating the crystalline nature of TMC with enthalpy fusion ∆H= 39.95 J/g(Shaker et al, 2014). The thermal analysis of Span 60 surfactant showed an endothermic peak at its melting point 59.32 °C with enthalpy fusion ∆H= 155.88 J/g (figure 4, A), whereas cholesterol showed also an endothermic peak at 51.56 °C with enthalpy fusion ∆H= 48.28 J/g (figure 3, B).…”
mentioning
confidence: 99%
“…Significant amount of research has been published to improve the bioavailability of Tamoxifen citrate by addition of cyclodextrin or solubility enhancers (Allan et al, 1985). Tamoxifen citrate loaded ternary solid dispersion was prepared using PEG 6000 and Methyl cellulose to enhance its bioavailability and solubility (Shaker, 2014). Through this type of formulations, not only the solubility of Tamoxifen citrate is enhanced but the side effect is also diminished.…”
Section: Introductionmentioning
confidence: 99%